Livelihood and survival strategies among Gweru urban teachers and their implications on pupils’ performance in the current Zimbabwe’s flopping economy - Muzvondiwa, Eresi (Technium Social Sciences Journal, 2020)
Currently, teachers’ salaries in Zimbabwe are insufficient to sustain the harsh economic situation yet teachers seem to be meeting their monthly livelihood demands. A study to explore different survival strategies engaged by teachers under this current flopping economy was conducted in the Gweru urban. A total of 55 participants were randomly selected from five different schools. Questionnaires and in-depth interviews were used to collect data. Descriptive statistics and Chi-Square test for association (SPSS version 21) were used to analyse the data. Findings revealed that teachers have adopted 15 survival strategies to augment their meagre salaries. Over 50% of the teachers indicated that borrowing money from banks/microfinance institutions, conducting extra lessons, poultry production, cross border trading, part-time teaching at private schools, production of horticultural produce and selling of goods (maputi “dried corn”, sweets, peanut butter, snacks etc...) were pillars to their survival in this collapsing economy. Gender influenced the adoption of cross border trading (?2 = 4.558; p <0.05) and hair dressing (?2 = 10.102; p <0.005). Delivery of extra lesson was significantly associated with job title (?2 = 5.026; p <0.05) constituting 70% teachers and 20% headmasters. It was observed that teachers with higher qualifications had a greater chances of being hired as part time private tutors in private schools. A greater proportion of the respondents (70.91%) agreed that venturing into these survival strategies impacted seriously on pupils’ overall performance. Thus teachers are recommended to balance their profession and private business to ensure that pupils’ performance is not compromised.